2021
DOI: 10.7554/elife.62585
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and transcriptomic profiling reveal different aspects of aging in the kidney

Abstract: Little is known about the molecular changes that take place in the kidney during the aging process. In order to better understand these changes, we measured mRNA and protein levels in genetically diverse mice at different ages. We observed distinctive change in mRNA and protein levels as a function of age. Changes in both mRNA and protein are associated with increased immune infiltration and decreases in mitochondrial function. Proteins show a greater extent of change and reveal changes in a wide array of biol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 50 publications
5
60
0
Order By: Relevance
“…By analyzing both transcripts and proteins in the mouse heart we were able to detect distinct biological processes that are altered through the course of natural aging. We and others have found that age-related transcriptional changes are not necessarily followed by a change in their proteins and likewise, age-related changes in proteins are not preceded by transcriptional changes (12,13,62,80). We found that transcripts decreasing in expression with age are associated with cardiomyocyte contraction and survival, and fatty-acid metabolism.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…By analyzing both transcripts and proteins in the mouse heart we were able to detect distinct biological processes that are altered through the course of natural aging. We and others have found that age-related transcriptional changes are not necessarily followed by a change in their proteins and likewise, age-related changes in proteins are not preceded by transcriptional changes (12,13,62,80). We found that transcripts decreasing in expression with age are associated with cardiomyocyte contraction and survival, and fatty-acid metabolism.…”
Section: Discussionsupporting
confidence: 51%
“…Age-related dysregulation of transcripts is offset by selective translation, and post-transcriptional mechanisms become crucial for achieving cellular homeostasis (11). The investigation of molecular mechanisms involved in aging is further complicated by the uncoupling of age-related changes between transcripts and their corresponding proteins (12). Waldera-Lupa et al (2014) found that 77% of the proteins that change with age in human fibroblasts showed no corresponding change in their transcripts (13).…”
Section: Introductionmentioning
confidence: 99%
“…To understand how expression of CGI + and CGI − genes (table S2) changes during aging, we performed RNA sequencing (RNA-seq) of kidneys and hearts from diversity outbred (DO) mice. DO mice are a genetically diverse mouse resource that mimics the complexity of the human population with variable rates of physiological aging ( 12 , 13 ). Figure 1B shows an example of gene expression in kidneys from 18- and 6-month-old mice, where 33.71% of CGI − genes were up-regulated over twofold in the aged kidney compared to the young kidney.…”
Section: Resultsmentioning
confidence: 99%
“…Since the phenotype of a senescent cell is dynamic and heterogeneous depending on the type of senescence inducer, and on the cell and tissue type, we compared our data with transcriptomic signatures characteristic of the aging kidney and senescent cells and/or SASP, in various cell types subjected to different methods of senescence induction (Fig. 4E) (58)(59)(60)(61)(62)(63)(64). The "senescence core signatures" identified by Hernandez-Segura et al (62) in fibroblasts, keratinocytes, melanocytes and astrocytes and by Casella et al (63) in fibroblasts and endothelial cells were not enriched in late injured cells.…”
Section: Merge With Bf/dapimentioning
confidence: 99%